Fabrication of Zinc Oxide Nanostructured Based Gas Sensor - Teow, Chee Suen; Dr. Amira Saryati Binti Ameruddin (Enhanced Knowledge in Sciences and Technology, 2023)
Zinc Oxide (ZnO) is a metal oxide semiconductor material that has been extensively studied and one of the promising materials for gas detection application. Compared to bulk materials, nanostructures with higher surface-to-volume ratio able to improved the performance of material in gas detection. In this study, ZnO nanorods and nanoflowers were synthesized by hydrothermal method, and their morphology-dependent gas sensing properties were investigated. Field Emission Scanning Electron Microscopy (FESEM) and Ultraviolet-visible (UV-Vis) spectrometer were used to confirm the properties of these two types of nanostructures. ZnO nanorods growth in alkaline solution have distinctively longer length nanorods clusters with hexagonally shaped tips. A cluster of short nanorods formed in the neutral solution. ZnO nanostructures exhibited good optical properties and main absorption peak at room temperature for ZnO nanoflowers is recorded around 380 nm and around 350 nm for nanorods. Although both morphologies have shown good sensitivity towards ethanol, the response of nanoflowers was higher than that of nanorods which was attributed to its relatively higher surface area and amount of surface defects. Furthermore, the electrode arrangement dependent gas sensing properties were investigated. The nanorods with interdigitated electrode have good response when deal with ethanol. Closely packed electrode of interdigitated has successfully enhanced the sensitivity of the device.